ANALISA FAKTOR PENYEBAB KERUSAKAN RUAS JALAN JAKENAN - WINONG KABUPATEN PATI - Hermawan, Matholiul Fatani; Rizani, Mohammad Debby; Yudaningrum, Farida (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
Roads are a transportation infrastructure that plays a very important role in the economic, social, political, defense and security fields. With the increasing number of vehicles, it is possible that the road will be damaged in a relatively short time. The Jakenan-Winong route can be said to be an alternative route that connects the Rembang-Pati areas. Jalan Raya Jakenan - Winong is included in the provincial road and according to road class it is included in the primary collector road. The purpose of this study, among others, is to determine the type of damage to the road using the Bina Marga Method, to identify the factors that cause road damage, and to find solutions to minimize damage to the road segment. Methods of data collection by observation or direct observation. The results of this study are: the total area of road damage is 2041.78 m2 or 0.1982310%. Consists of several types of damage, the most dominant is collapse with a total damage area of 250 m2 or 2.4271844% and an overall crack of 50.8 m2 or 0.4932038%. Based on an analysis of the condition of the types of road damage on the Jakenan-Winong road section, among others: subsidence, longitudinal cracks, edge cracks, slip cracks, loose grain, peeling of the surface layer, holes, patches, pavement edge damage. Of the many types of damage that occurred, the most common types of damage were collapse and cracks that occurred on these roads. The road damage factors are caused by excessive vehicle weight, poor implementation, material quality, poor drainage system, rainfall, soil and natural factors which damaged the Jakenan-Winong road. Repair solutions or handling strategies are carried out with corrective and maintenance actions in accordance with the type and level of damage that occurs on the Jakenan-Winong road section, each type and level of road damage requires repair and maintenance according to the damage. Repairs are made to restore comfort and safety for road users.